1993
DOI: 10.1002/1098-108x(199305)13:4<335::aid-eat2260130402>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in identity and self-regulation in bulimia nervosa: Implications for a metaphorical perspective of “body as self”

Abstract: This study investigates a metaphorical account of bulimia that proposes that bulimics lack a clearly defined sense of self, and subsequently utilize their physical bodies as a means of self‐definition and regulation. Three major aspects of this perspective were assessed: identity disturbance; use of the binge and purge as means of emotional regulation; and sensitivity to interpersonal contact. Differences among bulimics, binge eaters, and normal controls were explored. Bulimics reported greater amounts of iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 17 publications
(8 reference statements)
4
56
0
1
Order By: Relevance
“…First, emotional eating, that is, eating driven by emotions, is positively associated with identity confusion in patients with binge eating, and positively related to being female in patients without binge eating. These results is in line with earlier studies [29][30][31][32]37] which state that binge eating is a way to cope with the distress coming from identityrelated decisions. This is also confirmed by the finding that we found no significant relation between identity synthesis and emotional eating for those patients who engage in binge eating, suggesting that binge eating is not a way to cope with negative emotions in general, but is specifically used to deal with identity-related distress among those with a more confused identity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…First, emotional eating, that is, eating driven by emotions, is positively associated with identity confusion in patients with binge eating, and positively related to being female in patients without binge eating. These results is in line with earlier studies [29][30][31][32]37] which state that binge eating is a way to cope with the distress coming from identityrelated decisions. This is also confirmed by the finding that we found no significant relation between identity synthesis and emotional eating for those patients who engage in binge eating, suggesting that binge eating is not a way to cope with negative emotions in general, but is specifically used to deal with identity-related distress among those with a more confused identity.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that patients who engage in binge eating have a more confused identity than patients without binge eating, whereas no significant difference was found for identity synthesis. These results are in line with the findings of Schupack Neuberg and Nemeroff [30], who reported higher levels of identity diffusion in university students with binge eating. These findings also confirm prior studies which link the presence of identity confusion to more maladaptive psychological functioning [27,28], and eating disorder-related behaviors in particular [41].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Empirical research has consistently demonstrated that bulimic symptoms are associated with a host of interpersonal difficulties, [1][2][3][4][5][6][7][8][9] and that elevated interpersonal problems persist many years after an initial diagnosis. 10 Research also suggests that, like eating disorders themselves, the eating disorderinterpersonal problem relation is stronger in women than men, 11 and that women with bulimia nervosa tend to experience more interpersonal difficulties than women with anorexia nervosa.…”
Section: Introductionmentioning
confidence: 99%